The Oxford handbook of human resource management - Boxall, Peter F.; Purcell, John, 1945-; Wright, Pat. (Oxford University Press, 2008)
Human resource management is central to management teaching & research. Presenting the trends & developments, this handbook is divided into: foundations & frameworks; core processes & functions; patterns & dynamics; & measurement & outcomes.